Analysis of the Optic Nerve Head and Macular Ganglion Cell Complex Using Optical Coherence Tomography in Patients in the Post-COVID Period - I. V. Filonenko; Ya. V. Dorofeeva; E. B. Myakoshina (Oftalʹmologiâ, 2025)
Objective. To study the condition of the optic nerve head and the retinal ganglion cell complex (macula) using optical coherence tomography in patients in the post-COVID period.Patients and methods. A total of 30 people (60 eyes) aged 61.7 ± 14.2 years on average were examined. All subjects had a history of a new coronavirus infection (COVID-19). The duration of the disease ranged from 1.5 to 48 (26.9 ± 12.7 on average) months. The parameters of the optic nerve head and macula were assessed using the Optopol SOCT Copernicus REVO NX device (Poland).Results. Using OCT, the area of the optic nerve head, the area of the retinal ganglion cell complex, and the area of the optic nerve head excavation were significantly higher in patients in the post-COVID period compared to normal values (p < 0.05). The excavation volume of the optic disc of the left eye in patients in the post-COVID period was significantly lower than the norm (0.08 ± 0.07 and 0.15 ± 0.07, p = 0.003, respectively). The thickness of the peripapillary retinal nerve fiber layer in the upper quadrant of the right eye significantly exceeded normal values and amounted to 130.6 ± 17.7 (p = 0.03). Qualitative analysis of the state of the ganglion cell layer and the inner plexiform layer of the retina of the macula in individuals who had acute coronavirus infection showed that single areas of thinning were detected in 17 (28.3 %) of the 60 eyes examined, multiple — in 33 (55%).Conclusion. Of particular interest is the study using optical coherence tomography of the state of the optic nerve head, nerve fiber layer, and retinal ganglion cell complex of the macular zone in a significant number of patients who have had COVID-19. The obtained changes in the morphometric parameters of the fundus may indirectly indicate the neurotropic effect of the COVID-19 virus on the fundus structures, and requires examination of patients after infection to develop a rehabilitation system.